2011
DOI: 10.3343/kjlm.2011.31.3.148
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Quantitative Analysis of Cluster of Differentiation 45 Antigen Expression on Lymphocyte Subsets

Abstract: BackgroundSince the recent introduction of radioimmunotherapy (RIT) using antibodies against cluster of differentiation (CD) 45 for the treatment of lymphoma, the clinical significance of the CD45 antigen has been increasing steadily. Here, we analyzed CD45 expression on lymphocyte subsets using flow cytometry in order to predict the susceptibility of normal lymphocytes to RIT.MethodsPeripheral blood specimens were collected from 14 healthy individuals aged 25-54 yr. The mean fluorescence intensity (MFI) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Granulocytes were defined relative to the monocytes as SSC high /CD45 intermediate and found to comprise 17.9-47.8% of CD45 + cells. 26,53 Although these sample characteristics varied immensely (as previously re-ported 21,26 ) and did not correlate with the number of days postpartum at which the samples were obtained, the earliest sample analyzed, acquired 7 days after birth-previously defined as late colostral/early transitional milk-was the most cell dense and most replete with leukocytes. 26…”
Section: Sample Characteristicsmentioning
confidence: 84%
See 2 more Smart Citations
“…Granulocytes were defined relative to the monocytes as SSC high /CD45 intermediate and found to comprise 17.9-47.8% of CD45 + cells. 26,53 Although these sample characteristics varied immensely (as previously re-ported 21,26 ) and did not correlate with the number of days postpartum at which the samples were obtained, the earliest sample analyzed, acquired 7 days after birth-previously defined as late colostral/early transitional milk-was the most cell dense and most replete with leukocytes. 26…”
Section: Sample Characteristicsmentioning
confidence: 84%
“…A side scatter (SSC) versus CD45 plot was used to differentiate the major leukocyte classes (granulocytes, monocytes, and lymphocytes) as extensively described. 26,53 Percent of CD45 + cells and percent of each CD45 + subset were averaged from four wells and the data reported (Table 1) as meanstandard error. ADCP activity (bead-positive cells) was measured in the FITC channel.…”
Section: Measurement Of Adcpmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has, however, shown high level expression of CD45 on leukocytes within a relatively narrow range [29], indicating there is little interpersonal variation of CD45 antigen density in healthy adults. Similar work for the expression of CD227 on healthy adult epithelial cells has not been undertaken, although RNA analysis has shown strong expression in cultured oral epithelial cells [30].…”
Section: Discussionmentioning
confidence: 96%
“…Finally, MSCs co-cultured with CD45-positive cells, show an enhanced expression of specific genes, the markers of chondrogenic phenotype (41). CD45, also known as protein tyrosine phosphatase receptor type C, a type I transmembrane protein, is expressed in differentiated hematopoietic cells (42). In bone marrow, MSCs and hematopoietic stem cells co-exist and can be discerned with the presence of CD45.…”
Section: Cell-to-cell Interactionmentioning
confidence: 99%